V-shaped ion funnel proton transfer reaction mass spectrometry. Issue 4 (4th July 2019) - Wang, Yujie; Dong, Kexiu; Chu, Yannan
Abstract: A V-shaped ion funnel (IF) drift tube was developed for proton transfer reaction mass spectrometry (PTR-MS). The ion transmissions were characterized at variable radio frequency voltages and frequencies to obtain optimized conditions while considering the effects of radial-focusing, reaction rate, and collision-induced dissociation. The improvements in sensitivity for common compounds were experimentally obtained and ranges from 2 to 22 times depending on the analyte. The product ions distributions were also studied for V-shaped IF PTR-MS. Together with the literature reports for U-shaped IF PTR-MS, a valuable and comprehensive reference is provided for future optimization of IF PTR-MS and other mass spectrometers.